Project for Strengthening the Profile of Pancasila Students in Schools in Realizing the Sustainable Development Goal - Sri Jumini; Sudarsih Dwi Ningrum; Rifki Muntaqo; Abdurrohman Al Asy’ari (STAI Hubbulwathan Duri, 2025)
The rapid advancement of information and technology has influenced Indonesian students’ culture, mindset, and goal-setting strategies. The Pancasila Student Profile (PSP) is essential in 21st-century education, aligning with the Sustainable Development Goals (SDGs). This study aims to explore the implementation of the PSP in schools and identify the challenges in achieving SDGs. This research employs a quasi-qualitative approach, utilizing interviews, observations, and documentation for data collection. Data analysis follows the Miles and Huberman model, involving data reduction, data presentation, and conclusion drawing. The PSP Strengthening Project in schools contributes to SDGs through various activities: (1) producing anti-thirst fruit juice, fostering diversity, patriotism, cooperation, independence, creativity, and tolerance; (2) utilizing school land to cultivate sweet potatoes, promoting devotion to the creator, critical thinking, and creativity; and (3) creating pottery, enhancing diversity, patriotism, cooperation, and creativity. Obstacles in implementation include limited collaboration among educators, lack of teacher motivation, and time constraints. These challenges are addressed through socialization, collaboration, teacher motivation, Pancasila values reinforcement, ice-breaking activities, and coordinated scheduling with other subjects. The continuous reinforcement of the PSP through the P5 program significantly contributes to the realization of SDGs. Overcoming implementation challenges requires a systematic approach involving educators, students, and institutional support. The PSP plays a crucial role in fostering students' character development and achieving SDGs. Strengthening collaboration and optimizing instructional strategies are essential for overcoming challenges in implementing the P5 program.